Volume 3 2004
DOI: 10.1115/ht-fed2004-56597
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations Concerning Erosive Aggressiveness of Cavitation at Different Test Configurations

Abstract: The experimental results, which will be presented in this paper, demonstrate the significant influence of the flow velocity, respectively the rotational speed, on the erosive aggressiveness of cavitating flows. On two of the three investigated test objects, cavitation erosion can only be observed in the initial stage by the so-called pit-count evaluation method. Developed erosion with mass loss is impossible to measure because of the very long duration until mass loss appears. The third test rig generates a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition, the experimental cavitation numbers are higher for the higher velocities than those in the numerical model, which implies higher environment pressures and higher collapse efficiencies for higher velocities. Consequently, the erosion rate may increase with an exponent higher than 5, which would be in agreement with the experimental investigations by Dular et al, [40,41] who found that the erosion damage followed a power law with n values from 5 to 8.…”
Section: Appl Sci 2020 10 X For Peer Review 20 Of 23supporting
confidence: 91%
“…In addition, the experimental cavitation numbers are higher for the higher velocities than those in the numerical model, which implies higher environment pressures and higher collapse efficiencies for higher velocities. Consequently, the erosion rate may increase with an exponent higher than 5, which would be in agreement with the experimental investigations by Dular et al, [40,41] who found that the erosion damage followed a power law with n values from 5 to 8.…”
Section: Appl Sci 2020 10 X For Peer Review 20 Of 23supporting
confidence: 91%
“…18 Although the external characteristics of centrifugal pump do not change greatly at the initial stage of cavitation, cavitation will still cause pitting on the surface of impeller blade. 19 The significance of cavitation status monitoring is to determine the position of cavitation inception point as accurately as possible to avoid the operation of centrifugal pump in the quasi steady cavitation stage.…”
Section: Numerical Calculation Results and Analysismentioning
confidence: 99%
“…(1) Incipient Stage: In this stage, cavitation bubbles form and collapse in the blade inlet region, causing pitting damage to the blade [11].…”
Section: Cavitation Mechanismmentioning
confidence: 99%
“…(2) Weak Cavitation Stage: This stage encompasses the development of cavitation from its incipient state to the point of unstable cavitation occurrence [12]. Prolonged operation in a state of weak cavitation leads to surface damage in the overflow components, with the damage initiating on the blade inlet side and correlating with the length of the cavitation hole [11]. The scope of the weak cavitation stage can be determined through the analysis of the non-stationary dynamic properties.…”
Section: Cavitation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation